A novel energy-efficient and high speed full adder using CNTFET. (March 2017) - Mahani, Asma Torkzadeh; Keshavarzian, Peiman
Abstract: In the present paper, we will present two high speed, energy efficient and low power full adder circuits using gate diffusion input (GDI) cell, semi XOR/XNOR modules and carbon nanotube field effect transistors (CNTFET). Due to unique electrical and mechanical features of CNTFET, it can be chosen as an appropriate alternative to replace the metal oxide field effect transistors (MOSFET). In order to evaluate several figures of metric (FOM) including power consumption, energy consumption, propagation delay and energy delay product (EDP) using different voltage supplies, load capacitances, temperatures, frequencies and tubes, extensive experiments of proposed designs and previous works will be presented. Comparing to the previous works, simulation results of HSPICE illustrate the superiority of proposed designs regarding propagation delay and EDP.